2014
DOI: 10.1016/j.ypmed.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Association of environment and policy characteristics on children's moderate-to-vigorous physical activity and time spent sedentary in afterschool programs

Abstract: Background Afterschool programs (ASPs) are an important setting in which to promote children’s physical activity. This study examines the association of environmental and policy characteristics on the moderate-to-vigorous physical activity (MVPA) and sedentary behavior of children attending ASPs. Methods A total of 1,302 children attending 20 ASPs across South Carolina wore accelerometers (ActiGraph GT3X+) for up to 4 non-consecutive days. Policy-level characteristics were evaluated using the Healthy Aftersc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…The results contrasted with some previous studies which concluded that a policy promoting active play [ 31 ], recess [ 7 ], extracurricular activities [ 6 , 8 , 32 ], and general health through the HPS framework [ 33 ] was positively related to students’ overall PA. Additionally, other studies also showed a positive relationship between students’ total PA and multiple school PA policies (measured by a composite index) [ 34 , 35 ], and allowed student access to PA facilities outside school hours [ 36 ]. Nevertheless, our findings are consistent with some studies which demonstrated that school policies (measured by a composite index) were unrelated to students’ self-reported [ 37 ] or accelerometry-assessed PA [ 38 ]. Beets and colleagues found provocative results in their study as written school policy (promoting PA in general) had an inverse association with students’ PA [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results contrasted with some previous studies which concluded that a policy promoting active play [ 31 ], recess [ 7 ], extracurricular activities [ 6 , 8 , 32 ], and general health through the HPS framework [ 33 ] was positively related to students’ overall PA. Additionally, other studies also showed a positive relationship between students’ total PA and multiple school PA policies (measured by a composite index) [ 34 , 35 ], and allowed student access to PA facilities outside school hours [ 36 ]. Nevertheless, our findings are consistent with some studies which demonstrated that school policies (measured by a composite index) were unrelated to students’ self-reported [ 37 ] or accelerometry-assessed PA [ 38 ]. Beets and colleagues found provocative results in their study as written school policy (promoting PA in general) had an inverse association with students’ PA [ 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, this study did not account for the possible provision of sedentary activity options (e.g., children can choose from free play on playground or computer laboratory). Intuitively, scheduling more time for PA should be related to increased PA, but based on the findings from this study and others, 16 this might only occur when PA is the only option. This has important implications for practice, as small changes in program scheduling may lead to substantial increases in children's MVPA and decreases in time spent sedentary.…”
Section: Discussionmentioning
confidence: 68%
“…Estimates of the outdoor spatial area (acre) were calculated using Geographical Information Systems (GIS) software using standard protocols. 16 …”
Section: Program Characteristicsmentioning
confidence: 99%
“…Access to facilities promotes PA and therefore reduces SB ( 30 , 31 ). In the case of full-day schools, availability and access to the schoolyard or in some cases the school's own gym may help to encourage children for PA ( 32 ). Third, leisure time at home is often characterized by SB in the form of screen usage ( 33 ).…”
Section: Discussionmentioning
confidence: 99%